3.9k views
5 votes
Please answer correctly!!!!!

Please answer correctly!!!!!-example-1
User Janicelyn
by
6.3k points

2 Answers

1 vote

Answer:

B 259

Explanation:

The sum is 4 terms, so we need to add the 4 terms

Term 1: 6 ^ (1-1) = 6^0 = 1

Term 2: 6^ (2-1) = 6^1 = 6

Term 3: 6^ (3-1) = 6^2 = 36

Term 4: 6^ (4-1) = 6^3 =216

The sum is 1+6+36+216 = 259

User Prakash Boda
by
5.5k points
4 votes

The top number is 4 and t =1, so you need to replace t with 1, find the answer, then replace t with 2 through 4, then find the sum of all of them:


6^1-1 = 6^0 = 1

6^2-1 = 6^1 = 6

6^3-1 - 6^2 = 36

6^4-1 = 6^3 = 216


Sum = 1 + 6 + 36 + 216 = 259


The answer is B.

User Aldred
by
5.8k points